FIRM VALUE IN BANKING SECTOR : THE ROLE OF SIZE, PROFITABILITY, RISK PROFILE, AND DIVIDEND POLICY - Junika Halawa (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study explores how internal aspects of companies namely size, profitability, risk profile, and dividend impact firm value Indonesian banking sector listed on the IDX from 2013 to 2022. Using multiple linear regression analysis, the research analyzes 100 data points gathered from the financial statements of banking. The results indicate that both the company's size and its profitability significantly enhance firm value. In contrast, the risk profile has a detrimental effect, suggesting that higher risk undermines investor confidence. The dividend policy does not seem to have a meaningful effect, indicating it is not a vital factor for investors in this industry. These results highlight the necessity of maintaining operational effectiveness and financial soundness to boost the value of firms. This study offers empirical insights into the elements that affect firm value, particularly within the banking industry, and provides useful information for investors and managers to formulate effective strategies.